CASE REPORTSIncreased secretion of pleural fluid after ascending aortic dissection repair - Danielecki, Cezary; Bugajski, Paweł; Poprawka, Tomasz; Greberski, Krzysztof; Kalawski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
The patient was admitted to the Department of Cardiac Surgery of the J. Struś Municipal Hospital in Poznań due to dissection of the ascending aorta and arch. 7 days after the operation, which proceeded without complications, increased secretion of pleural fluid was revealed; the fluid was then evacuated repeatedly. The patient spent 52 days in hospital, including 22 days in the cardiac intensive care unit. Total drainage of the left pleural cavity amounted to 11 750 ml, and of the right – 4750 ml. The left pleural cavity was drained nine times, while the right was drained five times. The catheters from both pleural cavities were exchanged several times due to their obstruction. The patient was intubated five times because of deteriorating arterial blood gas results, and he required approximately 80 hours of mechanical ventilation. Thoracic surgery, radiological consultation, and chest CT did not reveal any tangible causes of that condition; therefore, only symptomatic treatment was applied.